The Victim–Offender Overlap in Sexual Offending: Exploring a Community-Based Sample of Young Adults in Hong Kong. (December 2021) - Chan, Heng Choon (Oliver)
This study examines the overlap between sexual offending perpetration and victimization among 1, 171 participants (18–40 years) in Hong Kong. Testing the theoretical propositions of several criminological theories (i.e., self-control, general strain, routine activity, and social learning), the participants' prevalence of general, penetrative, and nonpenetrative sexual offending perpetration and victimization are explored. The findings indicated that sexual offending perpetration and victimization are generally positively correlated, and further tests using multivariate analyses confirmed the relationship between these two experiences. Less than 5% of the sample had both sexual offending perpetration and victimization experience. The results of logistic regression indicated that participants who engaged in sexual offending were 1.67 times more likely to fall prey to sexual victimization. Similar odds ratio (1.67 times) was true for sexual victimization in predicting sexual offending perpetration. A bivariate probit model confirmed the sexual victim–offender overlap, with the Spearman's rho correlation from the unadjusted model suggesting significant overlap with general sexual offending (79%). Having a high level of risky sexual behavior was found to be a general risk factor for engaging in sexual offending behavior and for falling prey to sexual victimization.